Heme-Iron OptiFer® in the Treatment of Iron Deficiency Anemia During Pregnancy - Abdelazim, Ibrahim A.; AbuFaza, Mohannad; Al-Ajmi, Soud M.; Amer, Osama O.; Shikanova, Svetlana; Karimova, Bakyt (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVES: This study designed to compare the efficacy, and tolerability of heme-iron OptiFer® to ferrous fumarate in the treatment of iron deficiency anemia during pregnancy. STUDY DESIGN: Two hundred and thirty-four (234) women with iron deficiency anemia during pregnancy were included in this study; 121 women in the heme-iron OptiFer® group, and 113 women in the ferrous fumarate group. Women in the heme-iron OptiFer® group received OptiFer® tablets twice daily for ≥3 months then once daily as a maintenance dose. Women in the ferrous fumarate group received 350 mg oral ferrous fumarate once daily for ≥3 months. The pre-treatment ferritin, hemoglobin, red blood cells-mean corpuscular volume, and red blood cells-mean corpuscular hemoglobin were compared by the post-treatment values in the two studies. RESULTS: The post-treatment hemoglobin and ferritin were significantly high in the heme-iron OptiFer® group (11.2±7.1 gm/dL and 112.8±54.8 ug/l, respectively) compared to the ferrous fumarate group (10.9 ±5.1 and 89.9±43.3, respectively; p=0.0002 and p=0.006; respectively). The post-treatment red blood cells-mean corpuscular volume and red blood cells-mean corpuscular hemoglobin were significantly high in the heme-iron OptiFer® group (92.0±4.1 fl and 31.9±6.2 pg, respectively) compared to the ferrous fumarate group (87.7±2.9 and 28.5±4.7, respectively; p=0.0001 and p=0.001, respectively). The rates of poor compliance and gastrointestinal intolerance were significantly high in the ferrous fumarate group compared to the heme-iron OptiFer® group (12.4% and 19.5%, respectively versus 3.3% and 2.5%, respectively), (p=0.01 and p=0.0001, respectively). CONCLUSION: Heme-iron OptiFer® is an effective therapeutic option for the treatment of iron deficiency anemia during pregnancy with low side effects. heme-iron OptiFer® can be used in women who have low compliance, and/or gastrointestinal intolerance to conventional iron salts.